Efektivitas Larva Black Soldier Fly (Hermetia Illucens) dalam Mereduksi Pakan Limbah Organik Sawi Putih dan Daun Singkong - Maria Marselina Bay; Yardi Mantolas; Gonsianus Pakaenoni (Journal Science of Biodiversity, 2022)
Black Soldier Fly (BSF) is an insect that reduces organic waste by utilizing its larvae which will extract energy and nutrients from vegetable waste such as mustard and cassava leaves waste, fruits, food scraps, animal carcasses, and feces as food ingredients. This study aimed to see the effectiveness of BSF larvae in reducing feed organic waste of chicory and cassava leaves. The method used in this research is a laboratory and experimental scale experiment. The results of this study showed that the effectiveness of BSF larvae in reducing organic waste feed on cassava leaf waste samples was 57% for 1x3 feeding frequency, but decreased in 1x1 feeding frequency, which was 40%. While the percentage value of sample reduction by BSF larvae in chicory samples was 53% for 1x3 feeding frequency, but experienced a decrease in 1x1 feeding frequency, which was 38%. The effectiveness level of BSF larvae in reducing waste samples can be said to be effective at 1x3 feeding frequency.